Efektifitas Singer Sebagai Pelaksanaan Sanksi Adat dalam Hukum Perkawinan: (Studi Pada Komunitas Suku Dayak Bakumpai Di Kabupaten Barito Utara Kalimantan Tengah) - Ibrahim, Malik; Taufiqurohman, Taufiqurohman (STAINI Press, 2023)
Singer is a customary sanction contained in marriage problems among the Dayak Bakumpai indigenous people in North Barito Regency, Central Kalimantan in the form of traditional Dayak ceremonial equipment, slaughtering animals, gold, and agricultural products. This article wants to find out how far the effectiveness of the sanctions or singer fines is in tackling the occurrence of violations of marriage law in the Bakumpai Dayak community in North Barito Regency. Through qualitative research, it was concluded that Singer effectively maintains a family’s integrity. In addition, in general, Singer also plays a role in maintaining social balance, including marriage, adultery, ethics and morals, beliefs and beliefs, social responsibility, agreements, responsibility for the natural environment, adoption of siblings, property, accusations, theft, fights, and murder